The global disease burden attributable to a diet low in fibre in 204 countries and territories from 1990 to 2019. Issue 4 (23rd September 2022) - Zhuo, Ming; Chen, Ze; Zhong, Mao-Lin; Liu, Ye-Mao; Lei, Fang; Qin, Juan-Juan; Sun, Tao; Yang, Chengzhang; Chen, Ming-Ming; Song, Xiao-Hui; Wang, Li-Feng; Li, Yi; et al.
Abstract: Objective: The relationship of a diet low in fibre with mortality has not been evaluated. This study aims to assess the burden of non-communicable chronic diseases (NCD) attributable to a diet low in fibre globally from 1990 to 2019. Design: All data were from the Global Burden of Disease (GBD) Study 2019, in which the mortality, disability-adjusted life-years (DALY) and years lived with disability (YLD) were estimated with Bayesian geospatial regression using data at global, regional and country level acquired from an extensively systematic review. Setting: All data sourced from the GBD Study 2019. Participants: All age groups for both sexes. Results: The age-standardised mortality rates (ASMR) declined in most GBD regions; however, in Southern sub-Saharan Africa, the ASMR increased from 4·07 (95 % uncertainty interval (UI) (2·08, 6·34)) to 4·60 (95 % UI (2·59, 6·90)), and in Central sub-Saharan Africa, the ASMR increased from 7·46 (95 % UI (3·64, 11·90)) to 9·34 (95 % UI (4·69, 15·25)). Uptrends were observed in the age-standardised YLD rates attributable to a diet low in fibre in a number of GBD regions. The burden caused by diabetes mellitus increased in Central Asia, Southern sub-Saharan Africa and Eastern Europe. Conclusions: The burdens of disease attributable to a diet low in fibre in Southern sub-Saharan Africa and Central sub-Saharan Africa and the age-standardised YLD rates in a number of GBD regions increased from 1990 to 2019. Therefore, greater efforts are needed to reduce the disease burden caused by a diet low in fibre.